(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Tidal channels suitable for tidal power devel- opments exhibit complex, turbulent flow, at high Reynolds numbers with dynamic features over a wide range of scales that can persist for several hours. Modelling such flow plays a key part in characterising the conditions that tidal turbines will experience in situ. However, simulations of these channels are extremely challenging, and many numerical models compromise on either fidelity or size to keep computational complexity down to a manageable scale. New numerical techniques are required to overcome these restrictions, and provide the tidal energy industry with valuable insights into the marine environment. This paper presents a non-hydrostatic, high-fidelity com- putational fluid dynamics model of the Grand Passage in the Bay of Fundy, Canada, using the coastal and tur- bine modelling software CoastED. The model employs a Discontinuous Galerkin finite element formulation of the Navier-Stokes momentum equation, coupled with a Vreman subgrid eddy viscosity model, a variant of Large Eddy Simulation adapted for anisotropic grids. This, along with the use of a novel unstructured grid scheme, allows flow features from centimetres to kilometres to be captured over several M2 tidal cycles. By comparing virtual Acoustic Doppler Current Profiler (ADCP) results data with measurements from real ADCPs in the Grand Passage, we show that the model is effective in recreating aspects of the tidal currents often missed in hydrostatic simulations. We also examine some of larger modelled tidal flow features, and contrast them with evi- dence from satellite data.